Performance comparison of all-optical clocked S-R and D type flip-flops - Reis, C. (2013)
In this paper, different approaches to implement all-optical flip-flops, working with a synchronization signal, will be presented and compared. In this type of optical bistable devices, the information present at the inputs produces effects on the outputs, throughout all the clock pulse period. The performance of optical clocked flip-flops will be studied in terms of extinction ratio (ER), switching energies and switching times. © 2012 Elsevier GmbH.